Sensitivity analysis to produce anhydrous ethanol using pressure-swing system (Research, Society and Development, 2022)
Pressure-swing distillation is used to separate azeotropic mixtures without the addition of chemical compounds to the system. The objective of the present work was to perform a sensitivity analysis for the system composed by two distillation columns to produce anhydrous ethanol. The used thermodynamic models were validated through experimental data. The simulations were performed using the free software COFE and ChemSep. The operation parameters were evaluated considering the release of practically pure water at the bottom of the low-pressure column, and a bottom release of anhydrous ethanol for the high-pressure column. The final configuration of the system was, for the high-pressure column: 37 stages, fed at stage 14, with a reflux ratio of 0.380. For the low-pressure column: 32 stages, with the feed stream and recycle positioned on trays 30 and 14, respectively, and a reflux ratio of 4.250. The results and the discussion clarify the operation of the column and add knowledge to the separation process.